Melatonin in headache disorders - Gonçalves, Andre Leite; Ribeiro, Reinaldo Teixeira; Peres, Mario F. P. (Headache Medicine, 2012)
Melatonin have diverse physiological functions, including the control of circadian rhythms, sleep regulation, enhancement of immunological functioning, free radical scavenging and antioxidant effects, inhibition of oncogenesis, mood regulation, vasoregulation, regulation of seasonal reproductive activity and analgesia. Melatonin also have several actions within the central nervous system and in the pathophysiology of headaches, which include an anti-inflammatory effect, toxic free radical scavenging, reduction of proinflammatory cytokine up-regulation, nitric oxide synthase activity and dopamine release inhibition, membrane stabilization, GABA and opioid analgesia potentiation, glutamate neurotoxicity protection, neurovascular regulation, serotonin modulation, and the similarity of chemical structure to that of indomethacin. A relation with seasonal and circadian pattern has been observed in cluster an hypnic headache. The literature of headache is convergent in pointing to low levels of melatonin in patients with migraine and cluster headache. Treatment of headache disorders with melatonin and other chronobiotic agents is promising. Some trials showed that melatonin was effective in cluster headache and migraine prevention but future studies are necessary for the better understanding of the role of melatonin in headache disorders treatment.